Exploring Students’ Perception of EFL on the Use of ChatGPT to Complete the English Writing Task - Salwa, Athiyah; Tyas, Novita Kusumaning (Berumpun: International Journal of Social, Politics, and Humanities, 2024)
Like other AI technologies, ChatGPT is built to process questions with natural, human-like answers. Since its inception, ChatGPT has drawn a lot of pros and cons because it is widely used in the field of education and is considered to reduce the credibility of higher education. This study will describe and explore the perceptions of the use of ChatGPT by students in a descriptive quantitative manner. The participants in this study were students who attended English classes. They came from three different universities with a total of 150 respondents and a sample of 36 students. The instrument used was a questionnaire using a Likert scale. In addition, there are two additional questions to explore the reasons and suggestions of students on the use of ChatGPT. Questions are divided into three components. The first is whether ChatGPT increases students' learning motivation, the second is whether ChatGPT has features that are easy to access, and the last is whether ChatGPT can improve student performance and learning outcomes. The results of this study show that 62% of students agree that ChatGPT can increase student learning motivation because it provides insight into English Writing Skill classes. A total of 76% of students think that ChatGPT has features that are easy to use. Finally, 60% of students were able to improve student learning outcomes and performance in the English Writing Skill class.